Diseño de un modelo de simulación discreta para la mejora en la entrega de resultados de análisis fisicoquímicos en Laboratorios Incobra (2017)
In the present research project entitled as "Design of a discrete-event simulation model to improve the results delivery of physic-chemical analysis in laboratories INCOBRA" The physic-chemical analyses were characterized, and a data base was developed in the Excel tool with the operation times. Then, randomness and homogeneity tests were performed in the statistical programs Minitab and Statgraphics. In the input analyzer of the Arena software, goodness-of-fit tests was performed. After this, a simulation model was built with the support of Arena ® software and the above mentioned data to represent the arrival, analysis and results delivery process. The model was run 12 times to demonstrate whether it was statistically equivalent to the real-world system with confidence level equal to 95%. The results show that if the recommendations are followed, the number of analyzes carried out during the previous year would be increased in 44%.